2014
DOI: 10.1371/journal.pone.0103503
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Network Origins of Wealth Inequality: Insights from a Virtual World

Abstract: Almost universally, wealth is not distributed uniformly within societies or economies. Even though wealth data have been collected in various forms for centuries, the origins for the observed wealth-disparity and social inequality are not yet fully understood. Especially the impact and connections of human behavior on wealth could so far not be inferred from data. Here we study wealth data from the virtual economy of the massive multiplayer online game (MMOG) Pardus. This data not only contains every player's … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 41 publications
2
27
1
Order By: Relevance
“…3 (G, H) respectively. This agrees with Fuchs' result [44] that the output is correlated to both in-and out-degree. To avoid the impact of the in-and outdegree, we investigate the relation between the economic output y i and the position diversity d i of individuals with fixed k in , k out = 1, 3, 5 in Fig.…”
Section: Relationship Between Position Ratio Profiles and Economicsupporting
confidence: 92%
“…3 (G, H) respectively. This agrees with Fuchs' result [44] that the output is correlated to both in-and out-degree. To avoid the impact of the in-and outdegree, we investigate the relation between the economic output y i and the position diversity d i of individuals with fixed k in , k out = 1, 3, 5 in Fig.…”
Section: Relationship Between Position Ratio Profiles and Economicsupporting
confidence: 92%
“…The weak core identifies those individuals performing best in the virtual society. In previous studies, it has been shown that there is a direct relation between the degree of the player and its performance [22]. However, our findings indicate that nodes that are high social performers, well connected and part of a core group, need ties to other communities in the core.…”
Section: Discussioncontrasting
confidence: 50%
“…We demonstrate our idea with data from the MMOG society of the game Pardus (http://www.pardus.at) [16], an open-ended online game with a worldwide player base which currently contains more than 420,000 people. MMOGs have been shown to be exceptional platforms over which quantitative results about social structures, dynamics, and organisational rules can be derived [7,[16][17][18][19][20][21][22]. In this game players live in a virtual, futuristic universe where they interact with other players in a multitude of ways to achieve their self-posed goals.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time we know the players' exact positions at any point in time. The MMOG has been extensively studied as a human model society [4,[16][17][18][19][20][21][22][23][24]. Pardus has more than 430,000 players who "live" in a virtual environment and interact with each other in a multitude of ways.…”
Section: Introductionmentioning
confidence: 99%